Analisis Implemetasi Program Pelayanan Kesehatan Peduli Remaja (PKPR) Terhadap Kesehatan Mental Remaja di Puskesmas Kecamatan Mampang Prapatan Jakarta Selatan Tahun 2021 - Jessica Oktaviyani Patria (2021)
Adolescence is a period where various physical, emotional, and social changes are found. If we don't pay attention to this unique period, teenagers will become vulnerable to various problems such as risky behaviors, depression, suicide, etc. One of the Indonesian Government efforts to address the risks surrounding adolescent health is to develop a program known as the Youth Health Care Service (YHCS). The purpose of this study was to determine the implementation of the YHCS program based on the national standards guidelines in comparison to the mental health level of adolescents. This study uses a mixed method qualitative emphasized design. The sampling technique used in quantitative research is accidental sampling and in qualitative research is snowball sampling. The total sample obtained is 57 respondents and 4 informants. The results of the chi-square analysis showed that there was no relationship between sleep quality (p-value = 0.631), adequate family support (p-value = 0.710) and poor family support (p-value = 0.656) on adolescent mental health. However, adolescent's mental health was associated with adolescent's risky behavior (p-value = 0.044). YCHS services at Mampang Prapatan was found to have reached the national standard with an achievement rate of 91%, but there are various obstacles, especially in IEC and health promoting activities because of the pandemic situation. It is hoped that YHCS activities can be planned by involving youth in order to build a wider network.